K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 10 2018

Bài1: Phân tích các đa thức sau thành nhân tử

a)36-4x2+4xy-y2

\(=6^2-\left(4x^2-4xy+y^2\right)\)

\(=6^2-\left(2x-y\right)^2\)

\(=\left(6+2x-y\right)\left(6-2x+y\right)\)

b)2x4+3x2-5

\(=2x^4-2x^2+5x^2-5\)

\(=2x^2\left(x^2-1\right)+5\left(x^2-1\right)\)

\(=\left(2x^2+5\right)\left(x^2-1\right)\)

\(=\left(2x^2+5\right)\left(x-1\right)\left(x+1\right)\)

25 tháng 10 2018

B1:a)\(36-4x^2+4xy-y^2=36-\left(4x^2-4xy+y^2\right)=6^2-\left(2x-y\right)^2\)

\(=\left(6-2x+y\right)\left(6+2x-y\right)\)

c)\(a^3-ab^2+a^2+b^2-2ab=a\left(a^2-b^2\right)+\left(a-b\right)^2\)\(=a\left(a-b\right)\left(a+b\right)+\left(a-b\right)^2=\left(a-b\right)\left(a^2+ab+a-b\right)\)

d)\(x^2-\left(a^2+b^2\right)x+a^2b^2=x^2-a^2x-b^2x+a^2b^2\)\(=x\left(x-a^2\right)-b^2\left(x-a^2\right)=\left(x-a^2\right)\left(x-b^2\right)\)

e)\(x\left(x-y\right)+x^2-y^2=x\left(x-y\right)+\left(x-y\right)\left(x+y\right)\)\(=\left(x-y\right)\left(x+x+y\right)=\left(x-y\right)\left(2x+y\right)\)

22 tháng 8 2020

a, \(\left(x-y+1\right)\left(x+y+1\right)=x^2+xy+x-xy-y^2-y+x+y+1\)

\(=x^2+2x-y^2+1\)

b, \(\left(2x+3\right)^2+\left(2x-3\right)^2-2\left(4x^2-9\right)=4x^2+12x+9+4x^2-12x+9-8x^2+18\)

\(=36\)

1 tháng 11 2019

a) \(A=\left(3x+2\right)^2-9x\left(x+1\right)\)

\(A=9x^2+12x+4-9x^2-9x\)

\(A=3x+4\)

1 tháng 11 2019

\(B=\left(2x-1\right)^2-2\left(2x-1\right)\left(5x-1\right)+\left(5x-1\right)^2\)

\(B=\left[2x-1-\left(5x-1\right)\right]^2\)

\(B=\left(2x-1-5x+1\right)^2\)

\(B=\left(-3x\right)^2\)

\(B=9x^2\)

2 tháng 11 2016

câu 1 x-y=5

suy ra (x-y)2 = 25

x2 - 2xy + y2 = 25

-2xy = 25 - (x2 + y2)

-2xy = 10

xy = -5

ta có x3 - y3 = (x-y)(x2+xy+y2)=5(15-5)=5.10=50

 

câu2

(3x-1)2+2(3x-1)(2x+1)+(2x+1)2

=(3x-1+2x+1)2

=(5x)2

=25x2

 

 

21 tháng 12 2018

Bài 1 :

\(2x\left(x-5\right)+\left(x-5\right)=0\)

\(\Rightarrow\left(2x+1\right)\left(x-5\right)=0\)

\(\Rightarrow\orbr{\begin{cases}2x+1=0\\x-5=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{-1}{2}\\x=5\end{cases}}\)

KL :...

bài 2 :

\(x^2+6x+9-y^2=\left(x+3\right)^2-y^2\)

\(=\left(x+3-y\right)\left(x+3+y\right)\)

21 tháng 12 2018

Bài 3 :

\(P=\frac{3x^2+6x+12}{x^3-8}=\frac{3\left(x^2+2x+4\right)}{\left(x-2\right)\left(x^2+2x+4\right)}\)

\(=\frac{3}{x-2}\)

20 tháng 11 2016

x^4-y^4= (x^2)^2- (y^2)^2